1981
DOI: 10.3109/02713688109019976
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humour and plasma cortisol levels in glaucoma and cataract patients

Abstract: By means of radioimmunoassay, the content of endogenous cortisol in the aqueous humour and plasma of 35 patients suffering from various types of glaucomas and 35 cataract patients was determined, and the ratio of the plasma to the aqueous humour cortisol levels was calculated. The highest cortisol level in both plasma and aqueous humour was found to occur in patients with open-angle glaucoma suffering at the same time from systemic hypertension. The lowest plasma to aqueous humour cortisol ratio was found in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…Although still controversial, plasma and aqueous humor cortisol levels have been reported to be elevated in POAG patients [Rozsival et al, 1981;Schwartz et al, 1987;Stokes et al, 2003]. Further, although approximately 30-40% of the normal population, often referred to as \steroid responders," develop elevated IOP when treated with topical ocular glucocorticoids, the steroid responder rate is much higher in POAG patients [Clark and Morrison, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Although still controversial, plasma and aqueous humor cortisol levels have been reported to be elevated in POAG patients [Rozsival et al, 1981;Schwartz et al, 1987;Stokes et al, 2003]. Further, although approximately 30-40% of the normal population, often referred to as \steroid responders," develop elevated IOP when treated with topical ocular glucocorticoids, the steroid responder rate is much higher in POAG patients [Clark and Morrison, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Increased plasma cortisol, both total and free, as well as non-plasma glucocorticoids have been identified in OH and OAG compared with normals. [1][2][3][4][5][6] This present study was done on subjects hospitalized in a clinical study unit. This was in contrast to our previous studies on plasma cortisol levels, which were done on outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma cortisol levels have been shown to be increased in ocular hypertensives and open-angle glaucomas. [1][2][3][4][5][6] The increased level of plasma cortisol could be on the basis of an abnormality in the control mechanism for maintaining levels of plasma cortisol. A decrease in level of plasma cortisol stimulates the hypothalamic-pituitary complex to produce more ACTH, which, in turn, stimulates the adrenal cortex to increase the level of plasma cortisol.…”
mentioning
confidence: 99%
“…4C). Other studies detecting cortisol by RIA have reported values ranging from 4.8 to 49.7 nM (equivalent to 1.7-18.0 ng/ml) (20,21,29,30). Interestingly, the binding protein cortisol-binding globulin was not present at detectable levels (by RIA) (20).…”
Section: Discussionmentioning
confidence: 99%